Free vibration of symmetric angle ply truncated conical shells under different boundary conditions using spline method - Viswanathan, Kodakkal Kannan (Korean Society of Mechanical Engineers, 2015)
Free vibration of symmetric angle-ply laminated truncated conical shell is analyzed to determine the effects of frequency parameter and angular frequencies under different boundary condition, ply angles, different material properties and other parameters. The governing equations of motion for truncated conical shell are obtained in terms of displacement functions. The displacement functions are approximated by cubic and quintic splines resulting into a generalized eigenvalue problem. The parametric studies have been made and discussed